Stability of Alfvén eigenmodes in the China Fusion Engineering Test Reactor. (31st October 2019) - Ren, Zhen-Zhen; Chen, Yang; Fu, G.Y.; Wang, Zheng-Xiong
Abstract: The China Fusion Engineering Test Reactor (CFETR) is the next device in the Chinese roadmap for the realization of fusion energy, and is currently in the design phase. In this work, the stability of alpha particle-driven Alfvén eigenmodes (AEs) is investigated using a gyrokinetic ion/fluid electron hybrid code. It is found that the toroidal mode numbers of the most unstable modes are and the linear growth rate of the mode is slightly higher than that of the and modes. The excitation threshold in central alpha particle beta of the most unstable mode is found to be about, which is substantially below the expected value of alpha particle beta ( ) in CFETR. This result indicates that the high- n alpha particle-driven AEs are strongly unstable in CFETR, with many toroidal mode numbers simultaneously destabilized, at least for the CFETR design parameters considered in this work. Furthermore, a systematic study of parameter dependence has been carried out. It is found that the stability of AE with a single toroidal mode number is sensitive to the safety factor profile. However, the overall stability of AEs is much less sensitive to the value of when different toroidal mode numbers are considered simultaneously. It is shown that the normalized alpha particle gyro-radius and the alpha particle speed are two important parameters determining the alpha particle drive. The alpha particle drive is maximized for CFETR values of these two parameters. Finally, it is found that the alpha particle-driven AE's growth rate decreases as the thermal ion temperature/density decreases/increases at fixed plasma pressure.